Acute renal failure by rapidly progressive glomerulonephritis with IgA deposition in a patient concomitantly diagnosed with multibacillary Hansen's disease: a case report - Parente,Yuri de Deus Mont'alverne (2019)
ABSTRACT Rapidly progressive glomerulonephritis (RPGN) is a renal disease with an extensive differential diagnosis. This paper reports the case of a 55-year-old female patient diagnosed with Hansen's disease with acute progressive renal impairment after developing lower limb pyoderma. The association between Hansen's and kidney disease has been well documented, with glomerulonephritis (GN) ranked as the most common form of renal involvement. Post-infectious glomerulonephritis (PIGN) in adults has been associated with a number of pathogens occurring in diverse sites. The patient described in this case report had RPGN and biopsy findings suggestive of PIGN with C3 and IgA detected on immunofluorescence and kidney injury secondary to recent infection by Staphylococcus, a well-documented manifestation of renal impairment in patients with Hansen's disease.